2021
DOI: 10.1002/fsn3.2203
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of Se/Zn co‐supplementation on body weight and adipose tissue inflammation in high‐fat diet‐induced obese rats

Abstract: This research investigated the effect of co‐supplementation of selenium with zinc on weight control and the inflammatory and oxidative status in relation to obesity. Male Wistar rats (N = 32) were randomly divided into four groups after induction of obesity model: 1) “Zn” was supplemented with zinc sulfate (15 mg/kg BW), 2) “Se” supplemented with selenium as sodium selenate (0.5 mg/kg BW), 3) “Zn + Se” which received Zn (15 mg/kg BW) + Se (0.5 mg/kg BW), and 4) “HFD” as the control group. The intervention was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
(80 reference statements)
2
10
0
Order By: Relevance
“…Zinc has been shown to cause either an increase in body weight or a decrease depending on the basal weight of the subject [33,[56][57][58][59]. In this study methotrexate therapy resulted in significant weight loss corroborating the results of another study by Moghadam et al…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Zinc has been shown to cause either an increase in body weight or a decrease depending on the basal weight of the subject [33,[56][57][58][59]. In this study methotrexate therapy resulted in significant weight loss corroborating the results of another study by Moghadam et al…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the supplementation of zinc in methotrexate treated rats was associated with a concentration dependent decrease in body weight and food intake compared to control and a concentration dependent increase compared to methotrexate control. The effects of zinc on body weight and food intake have been reported severally [33,[56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increasing Se serum levels to 90.61 mg/L at the end of the intervention may indicate an improved selenoenzyme antioxidant activity in the group that received the Zn/Se co-administration. Some interesting findings by Hasani et al [82] are that the rats who received the highfat diet plus Zn significantly increased their Se serum levels and that a positive correlation was detected between Zn and Se serum levels. Furthermore, the co-supplementation of Se and Zn increased both Zn and Se serum levels [82].…”
Section: Discussionmentioning
confidence: 93%
“…When discussing the effects of Zn and Se supplements on RMR, the two micronutrients’ role on oxidative stress management should also be addressed due to the effect of oxidative stress on mitochondrial dysfunction. Hasani et al [ 82 ] examined the effects of Zn and Se co-supplementation in diet-induced obese rats. Thirty-two obese rats were divided into four groups and received either a high-fat diet alone or a combination of high-fat diet plus Zn, Se, or Se/Zn co-supplementation for eight weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we confirmed that the positive correlation between Se and Zn in the reproducible group was not observed in the repeat breeder group. Zinc also functions as an antioxidant and has a synergistic antioxidant effect with Se [ 55 ]. Therefore, in the case of a disrupted correlation between Se and Zn in hair minerals, simultaneously supplementing Se and Zn in the herd is recommended to increase antioxidant levels.…”
Section: Discussionmentioning
confidence: 99%